(untitled) (Jurnal Bina Praja, 2021)
This study aims to describe the government’s capability in waste management, problems, and alternative policies that can be made to overcome waste management problems in the city of Pekanbaru. This research uses a combination of quantitative and qualitative research methods. Quantitative methods describe the government’s capability in waste management by distributing questionnaires to lecturers, students, and alumni of the Environmental Science doctoral program at the University of Riau, environmental activists, and academics with master’s degrees who know about waste issues in the city of Pekanbaru. Qualitative research methods describe issues and policy alternatives by relying on document data from various literature ranging from journals, books, and online media, which are then analyzed using interactive data analysis methods. The results of quantitative data analysis show that the majority of respondents stated that the indicators of the Pekanbaru city government’s capability in managing waste transportation were the weakest technical and leadership skills. Furthermore, the results of qualitative data analysis show that the capacity factor and waste management issues can be overcome with several alternative policies. The problem of poor waste management can be overcome by using sustainable waste management, which needs to be supported by strong political will from the city government in making adequate regulations, updating waste management technology, utilizing information technology for waste transportation, and strengthening human resources. In addition, the government needs to involve the community and stakeholders to reduce waste production, collect waste, and sort waste. The support of the city government, entrepreneurs, and city residents will determine the success of sustainable waste management.